Lawless a criminal edition - Brubaker, Ed (Crimina, 2007)
"Twenty years ago, Tracy Lawless traded the crime-ridden streets of the city for a life in the military, and it?s a decision he?s rarely regretted. But now he?s walking out of the deserts of Afghanistan and Iraq and back into the world he came from, to find out who killed his brother Rick, and why. But truth is one of the few things uglier than family history, and the only thing Tracy has in his favor as he unravels the twisted strands of the criminal life his brother led, is that no on knows who the hell he is. And what they don?t know just might kill them" -- P. [4] of cover.